Short Communication: Endemics species of dung beetles (Coleoptera: Scarabaeidae) on the southern slope of Mount Slamet, Central Java, Indonesia - IMAM WIDHIONO; DARSONO DARSONO; NAILIL FASIHAH (Society for Indonesian Biodiversity, 2017)
Abstract. Widhiono I, Darsono, FasihahN.2017. Short Communication: Endemics species of dung beetles (Coleoptera: Scarabaeidae) on the southern slope of Mount Slamet, Central Java, Indonesia. Biodiversitas 18: 283-287.A survey was conducted to gauge the diversity of dung beetles (Coleoptera: Scarabaeidae) on the forested southern slope of Mount Slamet, Central Java, Indonesia, from April to June 2011. A total of 255 dung beetles of 14 species were collected. Of the 255 specimens collected, 125 (49.42%) were found in secondary forest and 130 (50.58%) were found in Agathis forest. The most abundant species was Phacosoma punctatum with 107 individuals (41.9%), followed by Onthophagus echinus with 53 individuals (20.7%) and Onthophagus palatus with 36 individuals (14.1 %). One species (Onthophagus trituber) was discovered to be a cosmopolitan species, while ten species (Onthophagus armatus, Onthophagus discedens, Onthophagus echinus, Onthophagus egenus, Onthophagus holzi, Onthophagus luridipennis, Onthophagus palatus, Onthophagus sp., Dactylosternum sp. and Apogonia cribrata) were endemic to Mount Slamet. Keywords: dung beetles, Mount Slamet, endemic species, cosmopolitan speciesÂ